Kerentanan Dan Ketahanan Petani Agroforestri Di Wilayah Lanskap Kepanewonan Tanjungsari, Kabupaten Gunungkidul, Yogyakarta - Kifli, Fahmi Wiryamarta; Falah, Muhammad Darul (Agricultural Socio-Economic Empowerment and Agribusiness Journal, 2025)
Farmers in Gunungkidul face two opposing sides: the vulnerability faced due to the harsh environment, and the extraordinary resilience in dealing with it. Located on karst slopes with barren soil and minimal water, they face great challenges in maintaining agricultural sustainability. Long and intense dry seasons often threaten crop yields. The karst landscape in Kapanewon Tanjungsari offers unique challenges and opportunities for agroforestry farming communities. The Tanjungsari karst landscape is faced with serious challenges related to the vulnerability and resilience of its livelihoods. The purpose of this study is to identify factors that influence community resilience and measure the level of vulnerability of agroforestry farmers. The approach taken in this study uses the Livelihood Vulnerability Index (LVI) approach, which is an approach from an index used to measure the level of vulnerability of a group or community to various risks or threats related to livelihoods and agroforestry practices carried out. The results showed that Ngestiharjo Village's Exposure level was lower than that of other villages, Hargosari Village's Sensitivity level was lower than that of other villages, and Ngestiharjo Village's Adaptation Strategy was higher than that of other villages. Overall, Ngestiharjo Village's LVI is better than Hargosari Village and Kemadang Village.